Examining the Impact of Organizational Culture and External Environmental Uncertainty on Management Control Systems - R. Sriristanti; Irwan Sutirman Wahdiat; Krisdiana Krisdiana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study aims to analyze the influence of organizational culture and external environmental uncertainty on management control systems (MCS) in companies in West Java. The dynamics of business competition and environmental changes demand that companies have adaptive and responsive management control systems. The research employs a quantitative approach with 72 respondents representing various managerial levels within companies in West Java. Data collection techniques involved surveys using both physical distribution and online (Google Forms), while data analysis utilized Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that organizational culture significantly influences the implementation of management control systems. Similarly, external environmental uncertainty also proves to affect management control systems. These findings reinforce contingency theory, which emphasizes the importance of aligning internal and external organizational factors to determine the effectiveness of management control systems. The practical implications of this research suggest that companies in West Java should strengthen the organizational values that encourage openness, innovation, and shared commitment, thereby enhancing the effectiveness of management control systems. Additionally, companies need to improve their adaptability to external environmental changes, including market dynamics, regulations, and technological developments. This study is expected to contribute theoretically to the literature on the impact of organizational culture and environmental uncertainty on the effectiveness of management control systems, and serve as a reference for practitioners to enhance company competitiveness.